2022 IEEE 21st Mediterranean Electrotechnical Conference (MELECON) 2022
DOI: 10.1109/melecon53508.2022.9842945
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sizing of a Community Level Thermal Energy Storage System

Abstract: Fifth-generation energy networks are combined networks of heat and electricity, that have the ability to generate, distribute, store and share energy between consumers. Knowledge on the dynamic behaviour of the physical phenomena related to energy generation, distribution and storage provides insight into the performance of the system as a whole. A mixed-integer linear algorithm is proposed, implementing a partitioned clustering program for subsequent classification of typical demand, grouping specific days wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Due to the growing interest in electrifying heat production, energy conversion devices, such as heat pumps, must be considered part of the ancillary services. Such devices also must be included at the individual level, as most energy networks do not allow sharing of heat between buildings [209]. HFCs can also generate heat, but this is a side effect of the process needing improvement to be fully deployed.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the growing interest in electrifying heat production, energy conversion devices, such as heat pumps, must be considered part of the ancillary services. Such devices also must be included at the individual level, as most energy networks do not allow sharing of heat between buildings [209]. HFCs can also generate heat, but this is a side effect of the process needing improvement to be fully deployed.…”
Section: Discussionmentioning
confidence: 99%
“…Including energy storage systems on the grid could reduce the adverse effects mentioned above [9], [10]. The technoeconomic study done by [11] demonstrated that installing BESS in the LV network can ensure voltage limits above 0.9 pu while representing only 77 % of the costs of upgrading the lines in the network to satisfy the voltage limit.…”
Section: Introductionmentioning
confidence: 99%